2013
DOI: 10.1155/2013/876503
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Case of Inflammatory Myofibroblastic Tumor in Maxilla

Abstract: Inflammatory myofibroblastic tumor (IMT) is a rare lesion found mostly in children and young adults and originates from the lung, abdominopelvic region, and retroperitoneum. Clinical manifestations of IMT or imaging are nonspecific and diagnosis is based on histopathological and immunohistochemical findings. Minority of all IMTs will metastasize. IMT in the oral cavity is an extreme rarity and this is a first case report of IMT in maxilla causing delayed tooth eruption and multiple cervical root resorption wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…The evidence of oral IMT in children was reported by Liston et al [ 5 ] where they described three cases 4 years, 2 years and 6 years, involving the buccal mucosa. Rautava et al [ 6 ] reported the case of an 11-year-old child with IMT involving the gingiva (maxilla buccal mucosa of 23 and 24) and Satomi et al [ 7 ] reported the case of a 14-year-old child with IMT involving the gingiva. To our knowledge, this is the first case report in the child where IMT was observed on the retromolar area.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence of oral IMT in children was reported by Liston et al [ 5 ] where they described three cases 4 years, 2 years and 6 years, involving the buccal mucosa. Rautava et al [ 6 ] reported the case of an 11-year-old child with IMT involving the gingiva (maxilla buccal mucosa of 23 and 24) and Satomi et al [ 7 ] reported the case of a 14-year-old child with IMT involving the gingiva. To our knowledge, this is the first case report in the child where IMT was observed on the retromolar area.…”
Section: Discussionmentioning
confidence: 99%
“…IMT of the upper jaw has been reported in an 11-year-old female by Rautava et al . [ 10 ] IMTs of upper aero-digestive tract are common in adults (median age of 59) and more often seen in the males. [ 11 ] In the present case the patient is a female of 36 years old.…”
Section: Discussionmentioning
confidence: 99%
“…Aðeins 24 tilfellum af vöðvabandvefsfrumuaexlum með bólgufrumuíferð í munnholi hefur verið lýst og einungis þremur í kinnkjálka. 2,3 Flest birt tilfelli hafa verið í lungum, kviðar-eða grindarholi og aftanskinnubili. Slík aexli utan lungna virðast sýna ágengari ífarandi vöxt í aðlaega vefi þó svo að myndun meinvarpa sé sjaldgaef í öllum tilfellum.…”
Section: Inngangurunclassified
“…Við skoðun var sjúklingur aumur við þreifingu yfir haegri kinn, í haegri nös, sem er þrengd af nefskiptaskekkju og að því er virtist miðlaegt hliðraðri nefskel, mátti sjá þrútnar slímhúðir án graftrartauma, en engin einkenni voru frá vinstri andlitshelmingi. Þegar haegri kinnhola var skoluð versnaði verkur til muna, án þess 1 Líffaerafraeði laeknadeildar Háskóla Íslands, 2 rannsóknarstofu í stofnfrumufraeðum við Lífvísindasetur Háskóla Íslands, 3 blóðmeinafraeðideild Landspítala, 4 lyfja-og eiturefnafraeðideild Háskóla Íslands, 5 meinafraeðideild Landspítala, 6 heilbrigðisog taugaverkfraeðisetur Háskólans í Reykjavík, 7 háls-, nef-og eyrnadeild Landspítala.…”
Section: Inngangurunclassified
See 1 more Smart Citation